Modelagem e simulação computacional da poluição do lago água preta - DIAS, Ariany Dias e (2022)
Differential equations constitute an important mathematical tool for the description of phenomena and processes, natural or artificial, in several areas of human knowledge. In this way, the present work uses an ordinary linear differential equation to model the pollution, by the element phosphorus, that occurs in the Água Preta lake, located in Belém do Pará. aid of the Wxmaxima software, through the use of symbolic computation to solve the analytical part and the nonlinear least squares method to make the numerical adjustment of the solution found previously to the real data obtained. This strategy showed that rainfall has great importance in the degree of pollution of the lake and that it has a periodic behavior.